Progesterone Receptor induces bcl-x expression through intragenic binding sites favoring RNA Polymerase II elongation - Bertucci, Paola Yanina (2013)
Steroid receptors were classically described for regulating transcription by binding to target gene promoters. However, genome-wide studies reveal that steroid receptors-binding sites are mainly located at intragenic regions. To determine the role of these sites, we examined the effect of pro- gestins on the transcription of the bcl-x gene, where only intragenic progesterone receptor-binding sites (PRbs) were identified. We found that in response to hormone treatment, the PR is recruited to these sites along with two histone acetyltransferases CREB-binding protein (CBP) and GCN5, leading to an increase in histone H3 and H4 acetylation and to the binding of the SWI/SNF complex. Concomitant, a more relaxed chromatin was detected along bcl-x gene mainly in the regions sur- rounding the intragenic PRbs. PR also mediated the recruitment of the positive elongation factor pTEFb, favoring RNA polymerase II (Pol II) elongation activity. Together these events promoted the re-dis- tribution of the active Pol II toward the 30-end of the gene and a decrease in the ratio between proximal and distal transcription. These results suggest a novel mechanism by which PR regulates gene ex- pression by facilitating the proper passage of the polymerase along hormone-dependent genes.